THE EFFECT OF PROFITABILITY, SOLVENCY AND LIQUIDITY ON COMPANY VALUE(Study on Mining Companies on the Indonesia Stock Exchange in 2020-2023) - Lembah, Amelia Amanda; Masruddin, Masruddin; Mapparessa, Nurlaela; Yuniar, Latifah Sukmawati (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This research aims to test and analyze simultaneously and partially the influence of profitability, solvency and liquidity on company value (Study of Mining Companies on the Indonesian Stock Exchange in 2020-2023). The population in this research is mining companies listed on the LQ 45 Index on the Indonesian Stock Exchange, totaling 11 companies. Sampling uses a saturated sampling technique so that the entire population is used as a sample. The data analysis method used is descriptive analysis and multiple linear regression using the SPSS 25 application. The results of this research show that simultaneously Profitability, Solvency and Liquidity have a significant and influential effect on Company Value. Meanwhile, partially Profitability and Liquidity have no effect on Company Value. Solvency has a negative influence on company value.